In-situ carbon-doped cobalt-based catalyst as well as preparation method and application thereof

The preparation of cobalt-based catalysts by in-situ carbon doping method solves the problems of poor conductivity and limited active sites of cobalt-based catalysts, and achieves the effect of improving electrochemical performance and reducing overpotentials. It is suitable for industrial applications of electrolyzing hydrogen production.

CN119592996AActive Publication Date: 2025-03-11SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411916934.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the process of electrolyzing the hydrogen production process of cobalt-based catalysts, there are problems such as limited number of active sites, poor conductivity and low intrinsic catalytic activity, which is difficult to meet the needs of industrial applications.

Method used

Cobalt-based catalyst is prepared by in-situ carbon doping method, and the organometallic frame precursor is prepared by hydrothermal method, and carbon is introduced through high-temperature calcination to solve the problem of poor conductivity.

Benefits of technology

It improves the conductivity and electrochemical properties of cobalt-based catalysts, reduces overpotentials, enhances catalytic activity, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592996A_ABST
    Figure CN119592996A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an in-situ carbon-doped cobalt-based catalyst, which comprises the following steps: mixing a metal source and an organic ligand to obtain a solid mixture, dissolving the solid mixture in a mixed solvent to obtain a mixed solution, the mixed solvent is composed of deionized water, ethanol and N, N-dimethylformamide; preparing an organic metal framework precursor from the mixed solution at 70-90 DEG C through a hydrothermal method; and calcining the organic metal framework precursor at 800-1000 DEG C, and naturally cooling to obtain the in-situ carbon-doped cobalt-based catalyst. The invention further relates to the in-situ carbon-doped cobalt-based catalyst and application thereof. The preparation method is simple, organic matter introduced by the organic ligand is calcined into carbon, and the carbon is doped into the cobalt-based material in situ, so that the problem of poor conductivity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrochemical catalyst, and more particularly to an in-situ carbon-doped cobalt-based catalyst and a preparation method and application thereof. Background Art

[0002] As a clean energy conversion technology, hydrogen production by water electrolysis is essential to meet the demand for renewable energy in modern society. Especially in the context of global energy structure transformation and reduction of greenhouse gas emissions, the demand for hydrogen energy as a clean and efficient energy carrier is growing. The oxygen evolution reaction (OER) occurring at the anode involves the transfer of four electrons, and the reaction barrier is high, requiring a highly active catalyst to reduce the overpotential.

[0003] Although noble metal-based materials such as platinum and iridium exhibit efficient catalytic activity in the oxygen evolution reaction (OER), their high cost and scarcity limit their large-scale application. Therefore, it is particularly urgent to develop non-noble metal catalysts with high activity, low cost and durability.

[0004] Cobalt-based catalysts have been widely used in the field of hydrogen production by water electrolysis due to their high activity and low cost. However, their performance still fails to meet the requirements of industrial applications due to their limited number of active sites, poor conductivity, and low intrinsic catalytic activity.

[0005] Metal-organic frameworks (MOFs) and their derivatives have shown great development potential in the field of new electrocatalysts due to their large specific surface area, rich pore structure, diverse composition and clear metal center. However, the low conductivity of MOFs materials has become a key technical bottleneck restricting their further application in the field of electrocatalysis. Summary of the invention

[0006] In order to solve the problems of low conductivity of metal organic frameworks in the above-mentioned prior art, the present invention provides an in-situ carbon-doped cobalt-based catalyst and a preparation method and application thereof.

[0007] According to one aspect of the present invention, a method for preparing an in-situ carbon-doped cobalt-based catalyst is provided, which comprises the following steps: S1, mixing a metal source and an organic ligand to obtain a solid mixture, dissolving the solid mixture in a mixed solvent to obtain a mixed solution, wherein the metal source comprises a cobalt salt, the organic ligand is 5-aminoisophthalic acid, and the mixed solvent consists of deionized water, ethanol and dimethylformamide; S2, preparing an organic metal framework precursor by a hydrothermal method (solvothermal method) at 70°C-90°C from the mixed solution; S3, calcining the organic metal framework precursor at 800°C-1000°C, and obtaining the in-situ carbon-doped cobalt-based catalyst after natural cooling.

[0008] In a preferred embodiment, the metal source further comprises manganese, nickel, chromium and / or iron salts. In a preferred embodiment, the cobalt salt is cobalt nitrate. In a preferred embodiment, the manganese salt is manganese chloride. In a preferred embodiment, the nickel salt is nickel nitrate. In a preferred embodiment, the chromium salt is chromium nitrate. In a preferred embodiment, the iron salt is iron nitrate.

[0009] In a preferred embodiment, the metal source is Co 2+ The molar ratio is 70%-100%, the metal source Ni 2+ , Fe 3+ ,Cr 3+ and / or Mn 2+ The molar ratio of Co is 0%-30%. 2+ The molar ratio of Co to Mn is 100%. In Example 2, the molar ratio of Co to Mn is 7:3, i.e., Co 2+ The molar ratio of Co to Ni is 70%. In Example 3, the molar ratio of Co to Ni is 7:3, i.e., 2+ The molar ratio of Co to Cr is 70%. In Example 4, the molar ratio of Co to Cr is 9:1, i.e. 2+ The molar ratio of Co, Ni and Mn is between 90% and 90%; in Example 5, the molar ratio of Co, Ni and Mn is 7:2:1, that is, Co 2+ The molar ratio of Co, Ni and Fe is 70%; in Example 6, the molar ratio of Co, Ni and Fe is 7:2:1, that is, Co 2+ The molar ratio is 70%.

[0010] In a preferred embodiment, the total amount of metal ions in the metal source (Co 2+ , Ni 2+ , Fe 3+ ,Cr 3+ and / or Mn 2+ ) and the molar ratio of the organic ligand is 0.0235:0.0703. In a preferred embodiment, the total amount of metal ions in the metal source is 23.5 mol.

[0011] In a preferred embodiment, the volume ratio of deionized water, ethanol and N,N-dimethylformamide in the mixed solvent is 1:1:1. In a preferred embodiment, 756 ml of the mixed solvent is composed of 252 ml of deionized water, 252 ml of ethanol and 252 ml of N,N-dimethylformamide.

[0012] In a preferred embodiment, ultrasound is applied until the solid mixture is completely dissolved in the mixed solvent.

[0013] In a preferred embodiment, in step S2, the mixed solution is transferred and added to a reactor, the reactor is sealed and placed in an oven, the oven is heated to 70°C-90°C for insulation, the oven and the reactor are cooled to room temperature, the reactor is opened, and centrifuged to obtain an organic metal framework precursor.

[0014] In a preferred embodiment, step S2 further comprises washing with deionized water and ethanol for three times respectively, drying naturally at room temperature, and grinding into solid powder with a mortar.

[0015] In a preferred embodiment, the reactor has a polytetrafluoroethylene liner.

[0016] In a preferred embodiment, the oven is gradually heated to 80°C at a rate of 5°C / min and operated at 80°C for 48 hours.

[0017] In a preferred embodiment, in step S3, the organic metal framework precursor is placed in a porcelain boat and calcined in an inert atmosphere in a tube furnace, and the temperature of the tube furnace is raised to 800° C.-1000° C. and then maintained at this temperature.

[0018] In a preferred embodiment, the tube furnace is heated to 800°C-1000°C at 8°C / min-10°C / min. In a preferred embodiment, the tube furnace is heated to 800°C at 9°C / min.

[0019] In a preferred embodiment, the temperature is kept at 10-30 min per gram of the organic metal framework precursor.

[0020] In a preferred embodiment, the inert gas is nitrogen or argon.

[0021] According to another aspect of the present invention, there is provided an in-situ carbon-doped cobalt-based catalyst obtained by the above preparation method.

[0022] According to another aspect of the present invention, there is provided the use of the above-mentioned in-situ carbon-doped cobalt-based catalyst in the production of hydrogen by alkaline water electrolysis.

[0023] In a preferred embodiment, the electrolyte is 1 mol / L KOH and the current density is 10 mA / cm 2 In this case, the overpotential is 340mV-355mV.

[0024] The preparation method of the in-situ carbon-doped cobalt-based catalyst according to the present invention is simple and can be mass-produced; the organic metal framework precursor is prepared by a hydrothermal method, the preparation temperature is low, the reaction time is short, energy saving and consumption reduction are achieved, and the obtained organic metal framework precursor has a very high carbon content, which provides a rich carbon source for the subsequent one-step pyrolysis method to prepare the in-situ carbon-doped cobalt-based catalyst; pyrolysis of the organic metal framework precursor is provided, and the organic matter introduced by the organic ligand is calcined into carbon and in-situ doped into the cobalt-based material to solve the problem of poor conductivity, while also solving the problem that other non-in-situ doping methods will destroy the original structure of the material, resulting in uneven distribution of doping elements, and the defects caused by doping will produce a large number of active sites; by integrating the characteristics of various metal element components, not only the application range of the metal organic framework is expanded to a certain extent, but also the diversity of its derivatives is expanded. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : is the X-ray diffraction pattern of the cobalt-based catalyst obtained according to Example 1 of the present invention.

[0026] Figure 2 : is the X-ray diffraction pattern of the cobalt-based catalyst obtained according to Example 2 of the present invention.

[0027] Figure 3 is a scanning electron microscope photograph of the cobalt-based catalyst obtained according to Example 2 of the present invention.

[0028] Figure 4 yes Figure 3 Magnified image of .

[0029] Figure 5 is a scanning electron microscope photograph of the cobalt-based catalyst obtained according to Example 3 of the present invention.

[0030] Figure 6 yes Figure 5 Magnified image of .

[0031] Figure 7 1 is the LSV polarization curve of the cobalt-based catalyst obtained according to Examples 1 to 6 of the present invention. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.

[0033] In this article, alkaline water electrolysis refers to the process of producing hydrogen by electrolyzing water in an alkaline electrolyte environment, and the electrolyte is generally a KOH solution with a mass concentration of 30%.

[0034] In this article, oxygen evolution reaction (OER) refers to a half-reaction in the water electrolysis reaction, which involves a multi-electron transfer process and has slow kinetics, and is a key factor restricting the efficiency of the entire water electrolysis device.

[0035] In this article, overpotential, also known as superpotential or overpotential, refers to the part of the actual voltage required to reach a certain current density in the electrocatalytic reaction that exceeds the theoretical voltage. The working potential in the actual reaction often needs to overcome the obstacles of the kinetic process and thus show a value higher than the equilibrium potential. The voltage exceeding the theoretical value is called overpotential, which is mainly used to overcome other resistances such as activation resistance and charge transfer resistance.

[0036] In this article, the anode catalyst refers to a catalyst that can promote electrochemical reactions. It can accelerate the oxygen evolution reaction at the anode, thereby improving the efficiency and speed of the electrochemical reaction.

[0037] In this article, the advantages of cobalt-based catalysts in hydrogen production by electrolysis of water are due to the high activity and variable valence of transition metal cobalt. Compared with precious metal-based catalysts, cobalt-based electrocatalysts have the advantages of abundant reserves, low cost and high catalytic activity and are widely studied.

[0038] In this article, in-situ doping refers to the direct addition of doping elements during the synthesis of the material. The doping elements and the main material are formed simultaneously during the synthesis process, which can better control the distribution and concentration of the doping elements and maintain the overall structure and performance of the material. In electrochemical tests, in-situ doped materials show better performance and long-term stability.

[0039] In this article, non-in-situ doping refers to synthesizing the material first and then introducing the doping element into the material. This method may destroy the original structure of the material and lead to uneven distribution of the doping element. In electrochemical tests, although it also shows certain electrochemical performance, it is usually not as stable and efficient as the in-situ doped material.

[0040] In this article, metal-organic frameworks (MOFs) refer to a class of crystalline porous materials with high specific surface area, high porosity and designable structure, which show great development potential as new electrocatalysts.

[0041] In this article, the hydrothermal method refers to a method of preparing materials in which water is used as a solvent in a reactor to dissolve and recrystallize the powder. The prepared powder has the advantages of complete grain development, small particle size and uniform distribution, and avoids the possible agglomeration of powder.

[0042] Example 1: Preparation of monometallic Co catalyst

[0043] Weigh 6.8472g (0.0235mol) of cobalt nitrate hexahydrate, add 12.7476g of 5-aminoisophthalic acid (0.0703mol) to obtain a solid mixture. Dissolve the solid mixture in a mixed solution consisting of 252ml deionized water, 252ml ethanol, and 252ml nitrogen-nitrogen dimethylformamide, and sonicate until the solid is completely dissolved. Transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave and place it in an oven, gradually heat the oven to 80°C at a rate of 5°C / min, and run at 80°C for 48h. After the oven insulation program is completed, the oven and the reactor are cooled to room temperature, the reactor is opened, and the solid obtained by centrifugation is a cobalt-based catalyst precursor, which is washed 3 times with deionized water and ethanol respectively, dried naturally at room temperature, and ground into a solid powder with a mortar. 1 g of solid powder was placed in a porcelain boat and calcined in a tube furnace under a nitrogen atmosphere. The temperature of the tube furnace was raised to 800°C at a rate of 9°C / min and kept at 800°C for 20 min. After the tube furnace was cooled naturally, an in-situ carbon-doped cobalt-based catalyst was obtained. Its X-ray diffraction pattern is shown in FIG. Figure 1 As shown, the cobalt-based catalyst corresponds to Co (card number 15-0806), and the diffraction peak at 2θ=26.5° corresponds to C (card number 26-1076). It can be seen that the cobalt-based catalyst obtained after high-temperature calcination is in-situ doped with carbon, thereby increasing the conductivity of the material through carbon doping and improving the electrochemical performance of the material.

[0044] Example 2: Preparation of bimetallic CoMn catalyst

[0045] Weigh 4.7930g (0.01646mol) of cobalt nitrate hexahydrate and 1.3968g (0.00706mol) of manganese chloride tetrahydrate, add 12.7476g of 5-aminoisophthalic acid (0.0703mol) to obtain a solid mixture. Dissolve the solid mixture in a mixed solution consisting of 252ml of deionized water, 252ml of ethanol, and 252ml of nitrogen-nitrogen dimethylformamide, and sonicate until the solid is completely dissolved. Transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave and place it in an oven, gradually heat the oven to 80℃ at a rate of 5℃ / min, and run at 80℃ for 48h. After the oven insulation program is completed, the oven and the reactor are cooled to room temperature, the reactor is opened, and the solid obtained by centrifugation is a cobalt-based catalyst precursor, which is washed 3 times with deionized water and ethanol respectively, dried naturally at room temperature, and ground into solid powder with a mortar. 1 g of solid powder was placed in a porcelain boat and calcined in a tube furnace under a nitrogen atmosphere. The temperature of the tube furnace was raised to 800°C at a rate of 9°C / min and kept at 800°C for 20 min. After the tube furnace was cooled naturally, an in-situ carbon-doped cobalt-based catalyst was obtained. Its X-ray diffraction pattern is shown in FIG. Figure 2As shown, the cobalt-based catalyst corresponds to Co (card number 15-0806) and Mn3Co7 (card number 18-0407), and the diffraction peak at 2θ=26.5° corresponds to C (card number 26-1076). It can be seen that the cobalt-based catalyst obtained after high-temperature calcination is in situ doped with carbon, thereby increasing the conductivity of the material through carbon doping and improving the electrochemical performance of the material. The scanning electron microscope photo of the cobalt-based catalyst is shown in Figure 3 and Figure 4 As shown. It can be seen that the particle size of the cobalt-based catalyst is micron-level and spherical, with a high specific surface area. The larger the specific surface area, the more active sites exposed on the surface of the catalyst powder, the better the catalytic performance, and ultimately improves the OER activity of the catalyst.

[0046] Example 3: Preparation of bimetallic CoNi catalyst

[0047] Weigh 4.7930g (0.01646mol) of cobalt nitrate hexahydrate and 2.0520g (0.00705mol) of nickel nitrate hexahydrate, add 12.7476g of 5-aminoisophthalic acid (0.0703mol) to obtain a solid mixture. Dissolve the solid mixture in a mixed solution consisting of 252ml of deionized water, 252ml of ethanol, and 252ml of nitrogen-nitrogen dimethylformamide, and ultrasonicate until the solid is completely dissolved. Transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave and place it in an oven, gradually heat the oven to 80°C at a rate of 5°C / min, and run at 80°C for 48h. After natural drying, grind it into a solid powder with a mortar. 1 g of solid powder was placed in a porcelain boat and calcined in a tube furnace under a nitrogen atmosphere. The temperature of the tube furnace was raised to 800°C at a rate of 9°C / min and kept at 800°C for 20 min. After the tube furnace was cooled naturally, an in-situ carbon-doped cobalt-based catalyst was obtained. The scanning electron microscope spectrum is shown in FIG. Figure 5 and Figure 6 As shown. It can be seen that the particle size of the cobalt-based catalyst is micron-level and spherical, with a high specific surface area. The larger the specific surface area, the more active sites exposed on the surface of the catalyst powder, the better the catalytic performance, and ultimately improves the OER activity of the catalyst.

[0048] Example 4: Preparation of bimetallic CoCr catalyst

[0049] Weigh 6.1624g (0.0212mol) of cobalt nitrate hexahydrate and 0.9409g (0.00235mol) of chromium nitrate nonahydrate, add 12.7476g of 5-aminoisophthalic acid (0.0703mol) to obtain a solid mixture. Dissolve the solid mixture in a mixed solution consisting of 252ml of deionized water, 252ml of ethanol, and 252ml of nitrogen-nitrogen dimethylformamide, and sonicate until the solid is completely dissolved. Transfer the mixed solution to the body of a polytetrafluoroethylene-lined high-pressure reactor, seal the reactor and put it into an oven, gradually heat the oven to 80℃ at a rate of 5℃ / min, and run at 80℃ for 48h. After the oven insulation program is completed, the oven and reactor are cooled to room temperature, the reactor is opened, and the solid obtained by centrifugation is a cobalt-based catalyst precursor, which is washed 3 times with deionized water and ethanol respectively, dried naturally at room temperature, and ground into solid powder with a mortar. 1 g of solid powder was placed in a porcelain boat and calcined at high temperature in a tubular furnace under a nitrogen atmosphere. The temperature of the tubular furnace was raised to 800°C at a rate of 9°C / min and kept at 800°C for 20 min. After the tubular furnace was naturally cooled, an in-situ carbon-doped cobalt-based catalyst was obtained.

[0050] Example 5: Preparation of ternary metal CoNiMn catalyst

[0051] Weigh 4.7930 g (0.01646 mol) of cobalt nitrate hexahydrate, 1.3680 g (0.00469 mol) of nickel nitrate hexahydrate, and 0.4680 g (0.00236 mol) of manganese chloride tetrahydrate, add 12.7476 g of 5-aminoisophthalic acid (0.0703 mol) to obtain a solid mixture. Dissolve the solid mixture in a mixed solution consisting of 252 ml of deionized water, 252 ml of ethanol, and 252 ml of nitrogen-nitrogen dimethylformamide, and ultrasonicate until the solid is completely dissolved. Transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave and place it in an oven, gradually heat the oven to 80°C at a rate of 5°C / min, and operate at 80°C for 48 hours. After the oven heat preservation program is completed, the oven and the reactor are cooled to room temperature, the reactor is opened, and the solid obtained by centrifugation is the cobalt-based catalyst precursor, which is washed with deionized water and ethanol three times respectively, dried naturally at room temperature, and ground into solid powder with a mortar. Take 1g of solid powder in a porcelain boat and calcine it at high temperature in a tubular furnace under a nitrogen atmosphere. The tubular furnace is heated to 800℃ at 9℃ / min, and kept at 800℃ for 20min. After the tubular furnace is cooled naturally, the in-situ carbon-doped cobalt-based catalyst is obtained.

[0052] Example 6: Preparation of ternary metal CoNiFe catalyst

[0053] Weigh 4.7930 g (0.0164 mol) of cobalt nitrate hexahydrate, 1.3680 g (0.0047 mol) of nickel nitrate hexahydrate, and 0.9557 g (0.0024 mol) of ferric nitrate nonahydrate, add 12.7476 g of 5-aminoisophthalic acid (0.0703 mol) to obtain a solid mixture. Dissolve the solid mixture in a mixed solution consisting of 252 ml of deionized water, 252 ml of ethanol, and 252 ml of nitrogen-nitrogen dimethylformamide, and ultrasonicate until the solid is completely dissolved. Transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave and place it in an oven, gradually heat the oven to 80°C at a rate of 5°C / min, and operate at 80°C for 48 hours. After the oven heat preservation program is completed, the oven and the reactor are cooled to room temperature, the reactor is opened, and the solid obtained by centrifugation is the cobalt-based catalyst precursor, which is washed with deionized water and ethanol three times respectively, dried naturally at room temperature, and ground into solid powder with a mortar. Take 1g of solid powder in a porcelain boat and calcine it at high temperature in a tubular furnace under a nitrogen atmosphere. The tubular furnace is heated to 800℃ at 9℃ / min, and kept at 800℃ for 20min. After the tubular furnace is cooled naturally, the in-situ carbon-doped cobalt-based catalyst is obtained.

[0054] Example 7: Testing the electrochemical performance of cobalt-based catalysts

[0055] A three-electrode system was constructed, and the in-situ carbon-doped cobalt-based catalysts of Examples 1 to 6 uniformly distributed on the hydrophilic carbon paper were used as working electrodes, and the catalyst loading was 3 mg / cm 2 ; The carbon rod was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the electrolyte was 1 mol / L KOH.

[0056] The LSV polarization curves of the cobalt-based catalysts obtained according to Examples 1 to 6 of the present invention are as follows: Figure 7 As shown, at a current density of 10 mA / cm 2 When the overpotential η of the bimetallic CoMn catalyst of Example 2 is 10 =E i -E t (theoretical voltage value) = 1.57-1.23 = 0.34 V = 340 mV, the overpotential η of the bimetallic CoCr catalyst of Example 2 10 =E i -E t =1.585-1.23=0.355V=355mV. Therefore, when the electrolyte is 1mol / L KOH and the current density is 10mA / cm 2 In this case, the overpotential is 340mV-355mV.

[0057] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A method for preparing an in-situ carbon-doped cobalt-based catalyst, characterized in that: The preparation method comprises the following steps: S1, mixing a metal source and an organic ligand to obtain a solid mixture, and dissolving the solid mixture in a mixed solvent to obtain a mixed solution, wherein the metal source includes a cobalt salt, the organic ligand is 5-aminoisophthalic acid, and the mixed solvent consists of deionized water, ethanol and dimethylformamide; S2, preparing an organic metal framework precursor by a hydrothermal method at 70°C-90°C from the mixed solution; S3, calcining the organic metal framework precursor at 800°C-1000°C, and obtaining an in-situ carbon-doped cobalt-based catalyst after natural cooling.

2. The preparation method according to claim 1, characterized in that: Metal sources also include manganese, nickel, chromium and / or iron salts.

3. The preparation method according to claim 2, characterized in that: Co of metal source 2+ The molar ratio is 70%-100%, the metal source Ni 2+ , Fe 3+ ,Cr 3+ and / or Mn 2+ The molar ratio is 0%-30%.

4. The preparation method according to claim 1, characterized in that: The volume ratio of deionized water, ethanol and N,N-dimethylformamide in the mixed solvent is 1:1:

1.

5. The preparation method according to claim 1, characterized in that: In step S2, the mixed solution is transferred and added into a reactor, the reactor is sealed and placed in an oven, the oven is heated to 70°C-90°C for insulation, the oven and the reactor are cooled to room temperature, the reactor is opened, and the organic metal framework precursor is obtained by centrifugation.

6. The preparation method according to claim 1, characterized in that: In step S3, the organic metal framework precursor is placed in a porcelain boat and calcined in an inert atmosphere in a tube furnace, and the temperature of the tube furnace is raised to 800° C.-1000° C. and then maintained at this temperature.

7. The preparation method according to claim 6, characterized in that: The tubular furnace was heated to 800°C-1000°C at 8°C / min-10°C / min.

8. An in-situ carbon-doped cobalt-based catalyst obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the in-situ carbon-doped cobalt-based catalyst according to claim 8 in hydrogen production by alkaline water electrolysis.

10. The use according to claim 9, characterized in that: The electrolyte is 1 mol / L KOH and the current density is 10 mA / cm 2 In this case, the overpotential is 340mV-355mV.

Citation Information

Patent Citations

  • Preparation method and application of N-Ni / N-CeO2 / nickel electrode

    CN114836788A

  • Co-loaded nitrogen-doped carbon nanotube electrocatalyst as well as preparation method and application thereof

    CN115896859A

  • Morphology-adjustable cobalt-based MOF catalytic electrode as well as preparation method and application thereof

    CN116426962A

  • Cobalt-copper-based electrolysis oxygen evolution catalyst and preparation method thereof

    CN117587440A